2008
DOI: 10.1593/neo.07724
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Warburg Effect in Early-Passage Breast Cancer Cells

Abstract: Malignancy in cancer is associated with aerobic glycolysis (Warburg effect) evidenced by increased trapping of [(18)F]deoxyglucose (FdG) in patients imaged by positron emission tomography (PET). [(18)F]deoxyglucose uptake correlates with glucose transporter (GLUT-1) expression, which can be regulated by hypoxia-inducible factor 1 alpha (HIF-1alpha). We have previously reported in established breast lines that HIF-1alpha levels in the presence of oxygen leads to the Warburg effect. However, glycolysis and GLUT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 77 publications
4
74
1
Order By: Relevance
“…This then combines with the promoter and enhancer on Glut-1 mRNA, leading to Glut-1 transcription to maintain the metabolism of tumor cells and supply them with a material foundation for further growth and metastasis. Glut-1 is mainly regulated by HIF-1α; however, it is also affected by other regulators (10).…”
Section: Discussionmentioning
confidence: 99%
“…This then combines with the promoter and enhancer on Glut-1 mRNA, leading to Glut-1 transcription to maintain the metabolism of tumor cells and supply them with a material foundation for further growth and metastasis. Glut-1 is mainly regulated by HIF-1α; however, it is also affected by other regulators (10).…”
Section: Discussionmentioning
confidence: 99%
“…Every year, millions of 18 F-FDG scans are conducted within the United States. Despite the tremendous promise and use of 18 F-FDG PET, a noticeable portion of these tumors, which are 18 F-FDG PET-negative, go undetected (6), possibly suggesting that some types of tumors are switching their metabolism and energy consumption from glucose to other nutrients, such as glutamine. Glutamine has the highest concentration (0.5-1 mM) among all of the amino acids circulating in the blood.…”
mentioning
confidence: 99%
“…This is the biochemical basis of using 18 F-FDG PET as a diagnostic tool for the detection of human cancers (9,10). Despite the utility of 18 F-FDG PET for staging and monitoring of cancer in humans, there is a growing realization that up to 30% of actively growing cancers are 18 F-FDG-negative and cannot be detected by 18 F-FDG PET (11). The observation strongly suggests that tumor cells may have alternative nutrient and metabolic strategies for survival and that glucose may not be the only source of energy and metabolic substrates for tumor growth (Fig.…”
mentioning
confidence: 99%
“…But, it is likely that using L-[5-11 C]-glutamine PET to study glutaminolysis might measure the additive effects of upregulation of glu-tamine transport and glutamine use. Similar to the tumor cell trapping of 18 F-FDG through upregulation of membranebound glucose transporter 1 and cytosol hexokinase, glutamine may be used via the glutamine transporter (ASCT2) and glutaminases located in the cytosol (9,11,18). Previously, 13 N-glutamine imaging of various spontaneous canine tumors showed that the imaging agent displayed a positive correlation with postmortem findings (20).…”
mentioning
confidence: 99%